La revue Santé mentale au Québec : des savoirs partagés en français - Lespérance, François (Santé mentale au Québec)

(untitled) (Revue Santé mentale au Québec, 2023)
The Revue Santé mentale au Québec (RSMQ) purpose is to contribute to the mental health knowledge dissemination and acquisition by adding much-needed cultural diversity to a scientific world community dominated by English-speaking journals. The RSMQ leadership wish to expand its societal impact and scientific outreach by working with its institutional partners to attract researchers and clinical practitioners across the world wishing to share their passions for learning in French.